Synthesis of 1,2,4-Trisubstituted 2-Imidazolin-5-Ones - Sobha, T.D.; Shafi, P.M. (Asian Journal of Chemistry, 2010)
Thirty five 4-arylidene-1,2-disubstituted-2-imidazolin-5-ones have been synthesized by the reaction between azalactones and amino compounds and derivatising the imidazolinones thus obtained.